دراسة الأسلوب الفكري لجرجي زيدان في مؤلفاته العربية التاريخية: Studying the Intellectual Style of Jurjī Zaydān in his Historical Arabic works (Al-Qamar, 2021)
This article sheds light on the life of Jurji Zidane and his scientific and literary status in modern Arabic literature. The study summarized that Jurji Zidane is a great historical novelist, with a prominent position in Arabic literature. He is famous for his Islamic historical novels. He is also known in the history of Arabic literature as the author of linguistic and historical works that he presented at the end of the nineteenth century and the beginning of the twentieth century. He presents in his novel’s European ideas of freedom, equality, and opinions about just laws. Rejection of class differences and women's liberation. All of this mixed with the ideas of the renaissance of Islam and the Arab world. Moreover, a new genre emerged for Arabic literature, which is the historical novel. That is why critics considered him among the writers and historians and made him one of the pioneers of journalism and writing.
Keywords: Illumination; vZāt-e-Aqdas; Hayāt Tayyaba; Islamic teachings